IMPOSED SUICIDES - VARDANYAN, KAMO (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
The scientific paper is devoted to one of the psychological displays of suicide – imposed suicides. Some types of imposed suicide are being suggested, preconditioned by tradition, law, disease, economic failures, criminal subcultures that cause the loss of a great number of people. The author introduces some theoretically grounded and practically tested approaches which will be useful for psychologists, doctors and will give the chance to foresee the coming act of suicide (suicide inevitability) and carry out precautionary (preventive) actions to prevent suicide and to provide treatment.
Keywords: : imposed suicides, suicides imposed by tradition, law, disease, economic failures, criminal subculture, that cause the loss of a great number of people